Answer :

Given: 3x = cosec θ , and 3/x = cot θ

Consider 3(x2 – (1/ x2)) =


= (1/3)(cosec2 θ – cot2 θ)

= 1/3 ( cosec2 x – cot2 x = 1)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Trigonometric IdentitiesTrigonometric IdentitiesTrigonometric Identities39 mins
Trigonometric Identities-IITrigonometric Identities-IITrigonometric Identities-II43 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses